Jahresbericht 1990 - Kunstgesellschaft Luzern. - Kunstmuseum Luzern, Luzern (Luzern : Kunstgesellschaft Luzern, 1991)
Thomkins, André ; Winnewisser, Rolf ; Wegman, William ; Laib, Wolfgang ; Lassnig, Maria ; etc.
Duits
boek